Alessandro De Gloria: 1955 - 2023 - Bellotti, Francesco; Baalsrud Hauge, Jannike; Gentile, Manuel; Jeuring, Johan; Marfisi-Schottman, Iza; Ninaus, Manuel; Veltkamp, Remco C.; Wanick, Vanissa; Berta, Riccardo (Serious Games Society, 2023)
The editorial of this issue of the International Journal of Serious Games is the last one signed by our Editor in Chief and Founder, Prof. Alessandro De Gloria. Alessandro passed away in Genova, Italy, on March 20th, few days after his 68th birthday. He founded the Serious Games Society and served as its first President, then as Honorary President. He founded also the Games and Learning Alliance Conference, of which he was the first General Chair and Honorary Chair. We mourn a great friend, and a pioneer researcher and creative teacher, with a broad, constructive vision and outstanding team-building skills. The good he made will remain in time.
Keywords: Serious games; Alessandro De Gloria; MSc program; Strategic engineering; Serious Games Society